The Oxford handbook of hedge funds - Cumming, Douglas,; Johan, Sofia A.,; Wood, G. (Oxford handbooks online., 2021)
A comprehensive overview of the hedge fund industry from a global perspective, bringing together insights from theoretical and applied research. The book seeks to both introduce the industry and what it does to scholars and practitioners new to the area, and to provide more advanced insights to those with extensive expertise in the area. The handbook explains the main context in which hedge funds operate, how the raise capital, and their structure and governance. It evaluates the main factors that have affected the operation of hedge funds, including competition from mutual funds, the market environment, and financial regulation, explains key concepts such as hedge fund flows, and core issues of practice, such as hedge fund manager fees.